2008
DOI: 10.1016/j.cell.2008.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Bleach Activates a Redox-Regulated Chaperone by Oxidative Protein Unfolding

Abstract: Summary Hypochlorous acid (HOCl), the active ingredient of household bleach, is an effective antimicrobial produced by the mammalian host defense to kill invading microorganisms. Despite the widespread use of HOCl, surprisingly little is known about its mode of action. In this study we demonstrate that low molar ratios of HOCl to protein cause oxidative protein unfolding in vitro and target thermolabile proteins for irreversible aggregation in vivo. As a defense mechanism, bacteria employ the redox-regulated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
383
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(399 citation statements)
references
References 33 publications
16
383
0
Order By: Relevance
“…(4,6,38). As has been shown for many other proteins, incubation of FGN or LDL with hypochlorite induces their self-aggregation into high-molecular mass complexes (1,39,40). In contrast, α 2 M is able to withstand high concentrations of hypochlorite without self-aggregating (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…(4,6,38). As has been shown for many other proteins, incubation of FGN or LDL with hypochlorite induces their self-aggregation into high-molecular mass complexes (1,39,40). In contrast, α 2 M is able to withstand high concentrations of hypochlorite without self-aggregating (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Our results support the conclusion that α 2 M is a specialized chaperone that prevents the extracellular accumulation of misfolded and potentially pathogenic proteins, particularly during innate immune system activity. molecular chaperone | inflammation | protein folding | clearance H ypochlorite, a potent oxidant produced by immune cells through the myeloperoxidase-H 2 O 2 -chloride system, kills invading microbes predominately by inducing the misfolding and aggregation of their proteins (1). The effects of hypochlorite, however, are nonspecific; therefore, when generated in vivo, the host organism suffers collateral damage (reviewed in refs.…”
mentioning
confidence: 99%
“…They govern the functions of various proteins, including redox-sensitive chaperone Hsp33 and calcium/calmodulin-dependent protein kinase CaMKII, through regulation of disulfide bond formation or oxidation of methionine residues (49,50). Oxidizing agents enhance the guanyltransferase activity of flavivirus NS5 or alphavirus nsP1 in vitro (51).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported oxidation-induced loss of secondary structure in several proteins (9,36,51,52). A recent study suggested oxidative unfolding and consequent aggregation as a major mechanism of HOCl-mediated protein inactivation (40). As sulfoxides are more hydrophilic than Met residues, their formation can change the overall surface charge of a protein (8,38).…”
mentioning
confidence: 99%